Nitrogen immobilization by Congo grass roots impairs cotton initial growth - Rosolem, Ciro Antonio [UNESP]; Steiner, Fábio [UNESP]; Zoca, Samuel Menegatti [UNESP]; Ducatti, Carlos [UNESP] (Canadian Center of Science and Education, 2012)
In crop-livestock integration systems the presence of both grass roots in the soil and straw on the surface can temporarily immobilize nitrogen. This study examined the persistence of grass residues in the system as well as their effects on cotton response to N when grown after Congo grass (Brachiaria ruziziensis, Syn. Urochloa ruziziensis). Congo grass was grown in pots with soil. Next, cotton was grown in the same pots without residues, with whole plant residues (Congo grass roots and shoots) or root residues (grass roots) and fertilized with N as ammonium nitrate. Congo grass and cotton roots were separated using stable carbon isotope fractioning. Congo grass roots showed higher C/N ratio than shoots, losing 14% of its mass after 45 days and increasing soil N immobilization. The lower N availability resulted in N deficient and shorter cotton plants with lower dry matter yields. Nevertheless, the application of 80 to 120 mg kg-1 of N compensated the immobilization by the soil microorganisms, allowing cotton to show normal growth. When Congo grass is present in the cropping system, the effects of the decaying roots on soil N dynamics and availability are more important than those of the straw left on the soil surface.
Keywords: Brachiaria ruziziensis; Gossypium hirsutum; Nitrogen fertilization; Roots; Soil N dynamics